Novel triazolopeptides: chirospecific synthesis and conformational studies of proline derived analogs - Paul, A.; Einsiedel, Jürgen; Waibel, Reiner; Heinemann, Frank Wilhelm; Meyer, Karsten; Gmeiner, Peter (Tetrahedron, 2009)
Replacing the backbone amide function by a heterocyclic bioisostere, [3+2] azide-alkyne cycloaddition has been applied for the construction of biologically relevant peptidomimetics. Starting from aminoalkynoates, triazole formation was accomplished by addition of hydrazoic acid. NMR studies displayed that the newly developed 4,5-triazolopeptides, which incorporate a biomimetic triazole NH-function as polar constraint element, showed a substantially higher tendency to form a cis-prolyl-geometry than a comparable native peptide sequence. © 2009 Elsevier Ltd. All rights reserved.